1994
DOI: 10.2307/1349465
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of Plant Variety Protection Certificates

Abstract: handicap. The Unlv8r8lty Is committed to-the maintenance of affirmative 'l!lCt1on .progr8ma' which will MIura,Iht cohtln\fation of euch equality of opportunity•.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
12
1
Order By: Relevance
“…First, plant variety certificates in industrialized countries have relatively low or negligible value. Lesser (1994) determined that the price premium associated with soybean certified seed was only 2.3 percent in New York State and concluded that this form of protection is too weak to be an incentive to breeders. Second, modern breeding programs are increasingly dependent on the use of "elite" breeding lines that are several generations removed from farmers' varieties and show increasingly complex pedigrees involving crop genetic resources from many sources .…”
Section: The International Treaty For Plant Genetic Resources For Foomentioning
confidence: 99%
“…First, plant variety certificates in industrialized countries have relatively low or negligible value. Lesser (1994) determined that the price premium associated with soybean certified seed was only 2.3 percent in New York State and concluded that this form of protection is too weak to be an incentive to breeders. Second, modern breeding programs are increasingly dependent on the use of "elite" breeding lines that are several generations removed from farmers' varieties and show increasingly complex pedigrees involving crop genetic resources from many sources .…”
Section: The International Treaty For Plant Genetic Resources For Foomentioning
confidence: 99%
“…Lesser (1994), with a hedonic analysis of 1992 soybean seed prices, finds that PVPCs are associated with a 2.3% increase in value. In wheat, PVPCs do not appear to allow firms to exercise significant market power (Alston and Venner 2002).…”
Section: Effectiveness Of Pbrsmentioning
confidence: 99%
“…Several studies of the use of crop germplasm (e.g., Marshall, 1989;Peeters & Galwey, 1988) suggest that current supplies in international and open collections exceed demand. The apparently low returns from plant variety protection in the United States are additional evidence of weak market potential for genetic resources (Lesser, 1994b). Adding contract costs to collection of new germplasm is almost certain to restrict demand even further, or to encourage users to make better use of other sources of germplasm.…”
Section: Market Failure In Valuing Genetic Resourcesmentioning
confidence: 99%